ANALISIS IMPLEMENTASI PEMBELAJARAN TATAP MUKA PASCA PANDEMI COVID-19 DI SMAN 2 MUSI RAWAS UTARA - CIndy SIntiya; Yantoro, Yantoro; Hendra, Robi (Indonesian Educational Administration and Leadership Journal (IDEAL), 2023)
This study aims to determine the implementation and obstacles faced in face-to-face learning after Covid-19 at SMAN 2 North Musi Rawas Regency. This research used qualitative methods with the research subjects of the principal and homeroom teacher of SMAN 2 North Musi Rawas. The data collection techniques used were observation, interview and documentation. The results showed that the implementation of learning after the Covid-19 pandemic at SMAN 2 North Musi Rawas was divided into three stages, namely the planning, implementation and evaluation stages and in each stage it was running quite well. In the planning & preparation stage, post-pandemic learning at SMA N 2 North Musi Rawas is carried out by still implementing health protocols. The planning stage carried out in the form of preparing annual programs, semester programs, lesson plans, and assessment plans and assessment plans. The obstacles that arise in the implementation of post-Covid-19 pandemic learning at SMAN 2 Musi Rawas Utara are very limited time and space. So that in the learning process the teacher lacks time to deliver the subject matter as usual to students who have more time. Another obstacle that arises in the implementation of post-pandemic learning is that the classroom atmosphere is not conducive, the level of politeness & discipline of students tends to decrease. Keyword: Learning, Offline, Post-Pandemic, covid-19